2009
DOI: 10.1021/jp902736z
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Vapor Removal by Cu3(BTC)2 and Its Characterization by MAS NMR

Abstract: Adsorption equilibria and NMR experiments were performed to study the adsorption and interactions of ammonia with metal-organic framework (MOF) HKUST-1, or Cu3(BTC)2 (BTC = 1,3,5-benzenetricarboxylate). Ammonia capacities determined from chemical breakthrough measurements show significantly higher uptake capacities than from adsorption alone, suggesting a stronger interaction involving a potential reaction with the Cu3(BTC)2 framework. Indeed, 1H MAS NMR reveals that a major disruption of the relatively simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
242
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(274 citation statements)
references
References 40 publications
27
242
5
Order By: Relevance
“…7 HKUST-1 (Cu 3 Btc 2 ) with the open Cu 2+ metal sites has been investigated for the removal of ammonia, nitric oxide, and CO 2 . [13][14][15][16] Ammonia uptake in HKUST-1 exceeds that of porous carbon. [13][14][15] However, the degradation associated with the presence of moisture renders HKUST-1 unsuitable for practical applications.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…7 HKUST-1 (Cu 3 Btc 2 ) with the open Cu 2+ metal sites has been investigated for the removal of ammonia, nitric oxide, and CO 2 . [13][14][15][16] Ammonia uptake in HKUST-1 exceeds that of porous carbon. [13][14][15] However, the degradation associated with the presence of moisture renders HKUST-1 unsuitable for practical applications.…”
Section: Introductionmentioning
confidence: 97%
“…[13][14][15][16] Ammonia uptake in HKUST-1 exceeds that of porous carbon. [13][14][15] However, the degradation associated with the presence of moisture renders HKUST-1 unsuitable for practical applications. [13][14][15][16][17] Therefore, probing co-adsorption of gases in MOFs with open metal center such as HKUST-1 is important.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…MOFs have an unprecedented ability to tailor functionality for targeted chemical interaction. Cu-BTC (also known as HKUST-1 or Cu 3 (BTC) 2 ) has been previously found to have an exceptionally high ammonia loading; however, this is at a cost of the material's structural stability 4 . Further studies on Cu-BTC have indicated that moisture itself is capable of degrading the MOF structure, rendering it ineffective for many potential applications 5,6,21 .…”
Section: Introductionmentioning
confidence: 99%
“…However, many MOFs with superior stability, such as UiO-66, have poor chemical removal capabilities, while many MOFs with open metal sites like MOF-74 and Cu-BTC have superior chemical removal capabilities 2,4,8,9 . The open metal sites in MOF-74 and Cu-BTC enhance the uptake of toxic gases such as ammonia, but these sites are also susceptible to binding water, poisoning the active sites and in many cases leading to structural breakdown.…”
Section: Introductionmentioning
confidence: 99%